The Emaciation Disease: The Possibility of Non-Pathogenic Occurrence in Olive Flounder (Paralichthys olivaceus) - Gyoungsik Kang; Won-Sik Woo; Bong-Jo Kang; Woon-Chul Kang; Chan-Il Park (Animals)
Emaciation disease has directly affected the production of olive flounder—a major aquaculture species in Korea—since the 2000s. Various myxosporeans have been reported as its causative agents. In this study, we investigated the recent resurgence of emaciation on Jeju Island, considering not only myxosporean infections but also potential environmental factors. Unlike previous studies that have primarily attributed the causes of emaciation disease to infections by myxosporeans, this research aimed to determine whether pathogen infection is indeed the sole cause of emaciation disease through molecular and histopathological analyses. Molecular biological and histopathological analyses of aquaculture and laboratory samples revealed that gross pathology lesions of emaciation can occur in the absence of pathogens, as well as in environments with myxosporean infections. These findings suggest that emaciation disease can be exacerbated by certain environmental factors in addition to myxosporeans. Future research should focus on detailed experimental designs to identify the specific environmental conditions contributing to the severity of this disease.